Role of Enterococcus faecalis in refractory apical periodontitis: from pathogenicity to host cell response. Issue 1 (31st December 2023) - Deng, Zilong; Lin, Binbin; Liu, Fan; Zhao, Wanghong
ABSTRACT: Background: Refractory apical periodontitis (RAP) is an oral infectious disease characterised by persistent inflammation, progressive alveolar bone destruction, and delayed bone healing. RAP has received increasing attention, because it cannot be cured after repeated root canal therapies. The aetiology of RAP is related to the complex interplay between the pathogen and its host. However, the exact pathogenesis of RAP remains unclarified and includes several factors, such as microorganism immunogenicity, host immunity and inflammation, and tissue destruction and repair. Enterococcus faecalis is the dominant pathogen involved in RAP, and has evolved multiple strategies to ensure survival, which cause persistent intraradicular and extraradicular infections. Objective: To review the crucial role of E. faecalis in the pathogenesis of RAP, and open new avenues for prevention and treatment of RAP. Methods: The PubMed and Web of Science databases were searched for pertinent publications, employing the search terms "Enterococcus faecalis", "refractory apical periodontitis", "persistent periapical periodontitis", "pathogenicity", "virulence", "biofilm formation", "dentine tubule", "immune cell", "macrophage", and "osteoblast". Results and Conclusion: Besides its high pathogenicity due to various virulence mechanisms, E. faecalis modulates the macrophage and osteoblast responses, including regulated cell death, cell polarisation, cell differentiation, and inflammatory response. An in-depth understanding of the multifaceted host cell responses modulated by E. faecalis will help to design potential future therapeutic strategies and overcome the challenges of sustained infection and delayed tissue healing in RAP.